2002
DOI: 10.1007/s002340100690
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced MR angiography (enhanced 3-D fast gradient echo) for diagnosis of cerebral aneurysms

Abstract: We evaluated contrast-enhanced MRA (enhanced 3-D fast gradient echo, EFGRE3D, with spectral IR) for the identification of unruptured cerebral aneurysms. We examined 22 aneurysms from 15 patients. In its ability to identify aneurysms, contrast-enhanced MRA was superior to 3-D-time of flight (3D-TOF) MRA in 4 instances, equal in 17, and inferior in 1. Contrast-enhanced MRA demonstrated thrombus formation more clearly and accurately than did 3D-TOF MRA. Contrast-enhanced MRA was performed in less than 1 min, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Ultrafast CE-MRA sequences are rapid, permit excellent spatial resolution and better visualization of peripheral intracranial circulation, 30 are less susceptible to spin dephasing and saturation, 11,26 and readily depict the presence of aneurysms. 31,32 However, several reports have concluded that CE-MRA has no additional benefit over 3D TOF-MRA for the depiction of residual aneurysm on follow-up imaging after treatment with GDCs. 14,17,27 Previously, Cottier et al 14 used a 3D TOF-MRA sequence with and without the administration of intravenous contrast material and found no improvement in the depiction of residual or recurrent aneurysm with contrast agent.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrafast CE-MRA sequences are rapid, permit excellent spatial resolution and better visualization of peripheral intracranial circulation, 30 are less susceptible to spin dephasing and saturation, 11,26 and readily depict the presence of aneurysms. 31,32 However, several reports have concluded that CE-MRA has no additional benefit over 3D TOF-MRA for the depiction of residual aneurysm on follow-up imaging after treatment with GDCs. 14,17,27 Previously, Cottier et al 14 used a 3D TOF-MRA sequence with and without the administration of intravenous contrast material and found no improvement in the depiction of residual or recurrent aneurysm with contrast agent.…”
Section: Discussionmentioning
confidence: 99%
“…With advances in MDCT technology and high-performance CT scanners, CTA has been established as a valid noninvasive imaging technique for screening and characterization of intracranial aneurysms [27][28][29]. Contrastenhanced MR angiography also has gained wide acceptance for evaluation of intracranial aneurysms [14][15][16][17]. Because of its speed, lack of sensitivity to flow-related artifacts (spin saturation and phase dispersion), and capability of covering a large field of view, contrastenhanced MR angiography has inherent advantages over time-of-flight MR angiography [30,31] and is a practical alternative to CTA.…”
Section: A-d Coronal Oblique 2d Multiplanar Reformation and 3d Volummentioning
confidence: 99%
“…With the introduction of and advances in minimally invasive crosssectional techniques such as CT angiography (CTA) and MR angiography, the clinical approach to suspected cerebral aneurysm has changed substantially. CTA has been used successfully for evaluation of intracranial aneurysms [14][15][16]. The success of CTA is in large part due to its speed and high spatial resolution, and advances in MDCT technology have raised the bar for other alternative noninvasive imaging techniques.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent studies have compared contrast-enhanced MRA with other MRA protocols for the evaluation of this pathology. Suzuki et al [12] studied 22 aneurysms from 15 patients, and found that contrast-enhanced MRA (enhanced fast gradient echo 3D, EFGRE3D) was superior to 3D TOF MRA in 4 cases, while it was equivalent in 17 cases and inferior in 1 case. Furthermore, contrastenhanced MRA had a significantly shorter acquisition time (<1 min) and thus was more feasible in these patients.…”
Section: Cerebral Aneurysmsmentioning
confidence: 99%